Pricing and Firm Conduct in California's Deregulated Electricity Market - Puller, Steven L. (The Review of Economics and Statistics, 2007)
This paper analyzes the pricing behavior of electricity generating firms in the restructured California market from its inception in April 1998 until its collapse in late 2000. Using detailed firm-level data, I find that conduct is fairly consistent with a Cournot pricing game for much of the sample. In summer and fall 2000, the market was slightly less competitive, yet the dramatic rise in prices was more driven by changes in costs and demand than by changes in firm conduct. The five large nonutility generators raised prices slightly above unilateral market-power levels in 2000, but fell far short of colluding on the joint monopoly price.